METHOD OF JUSTIFICATION OF THE NECESSARY NUMBER OF ENVIRONMENTAL MONITORING TOOLS AND OPTIMIZATION OF THEIR LOCATION PLACES - ДЕРМАН, В. А.; СУКАЛО, М. Л. (Technologies and Engineering, 2023)
Introduction. In modern conditions, an urgent issue for Ukraine is the development of a methodology for substantiating the locations of mobile ecological laboratory bases and their composition, which will allow for limited time monitoring of territories affected by hostilities, potentially dangerous objects (PDO) and about objects of critical infrastructure (OCI). Purpose. Mobile environmental laboratories in the region should be located to minimize the costs of monitoring and responding to time-limited emergencies. Methodology. The existing bases of environmental monitoring means should be considered as initial conditions for creating a methodology for solving this problem of optimizing the placement of mobile environmental laboratories in the territories immediately adjacent to the areas of hostilities. Findings. The results of the research can be used in the development of recommendations for choosing the optimal placement of unmanned aircraft complex (UAC) and their infrastructure on the territory of Ukraine in the context of reforming and reducing the number of aviation. A well-grounded choice of a section of the region's territory for the deployment of UAC will increase the level of technogenic and environmental safety during work on the prevention, monitoring and elimination of emergencies of a natural and technogenic nature. Originality. The results of the research can be used in the development of recommendations for choosing the optimal placement of UAC and their infrastructure on the territory of Ukraine in the context of reforming and reducing the number of aviation. A well-grounded choice of a section of the region's territory for the deployment of UAC will increase the level of technogenic and environmental safety during work on the prevention, monitoring and elimination of emergencies of a natural and technogenic nature. Practical value. Thus, the example of the practical application of the method of substantiating the required number of forces and means of environmental monitoring of operational zones and areas of hostilities is carried out according to the criterion of the minimum number of forces and means used, provided that the full scope of monitoring works is performed. The article provides a mathematical formulation of the problem for the development of the methodology and an example of its calculation for determining the location of mobile ecological laboratories using unmanned aerial vehicle complexes.